Tooth and claw - Walton, Jo (TOR, 2019)
Walton returns with Tooth and Claw, a very different kind of fantasy story: the tale of a family dealing with the death of their father, of a son who goes to law for his inheritance, a son who agonizes over his father's deathbed confession, a daughter who falls in love, a daughter who becomes involved in the abolition movement, and a daughter sacrificing herself for her husband. Except that everyone in the story is a dragon, red in tooth and claw. Here is a world of politics and train stations, of churchmen and family retainers, of courtship and country houses...in which, on the death of an elder, family members gather to eat the body of the deceased. In which society's high-and-mighty members avail themselves of the privilege of killing and eating the weaker children, which they do with ceremony and relish, growing stronger thereby.